Giant renal angiomyolipoma (RAML): a case report and literature review - Nasim, Ahsan; Adeena Azam; Mufti, Amna Faheem; Hafiz Usman Azeem (Journal of the Pakistan Medical Association, 2025)
Renal angiomyolipoma is a benign, rare type of tumour which consists of mature adipose tissue, thick-walled blood vessels, and smooth muscle cells. This tumour can grow to a large size, and is then defined as giant. We are describing the case of a 34-year-old female with a giant renal angiomyolipoma, measuring 32cm x 28cm x 6cm, which caused her pain and constipation. The mass was removed successfully, and partial nephrectomy was done. The patient had an uncomplicated postsurgical clinical course, and renal function was preserved. Renal angiomyolipoma is a hamartomatous, benign mass with variable components. It can occur sporadically or in association with genetic syndromes such as tuberous sclerosis. Symptoms include abdominal pain and constipation. Potentially dangerous sequelae include retroperitoneal haemorrhage and shock. The treatment for these tumours is surgery with open nephrectomy. Other treatment modalities have also been developed. Diagnostic workup should be done for genetic syndromes whenever necessary. Keywords: Angiomyolipoma, Renal angiomyolipoma, RAML, Tumour.